Advanced district heating and cooling (DHC) systems - Wiltshire, Robin (Amsterdam ; Boston : Elsevier : WoodHead Publishing, 2016)
Advanced District Heating and Cooling (DHC) Systems presents the latest information on the topic, providing valuable information on the distribution of centrally generated heat or cold energy to buildings, usually in the form of space heating, cooling, and hot water. As DHC systems are more efficient and less polluting than individual domestic or commercial heating and cooling systems, the book provides an introduction to DHC, including its potential contribution to reducing carbon dioxide emissions, then reviews thermal energy generation for DHC, including fossil fuel-based technologies, those based on renewables, and surplus heat valorization. Final sections address methods to improve the efficiency of DHC.
''3.6.1.3 Connection to the electricity network''''3.6.1.4 Fuel transfer on the conveyor'';''3.6.1.5 Fuel gasification'';''3.6.1.6 Gas cooling'';''3.6.1.7 Gas cleaning'';''3.6.1.8 Ashes'';''3.6.1.9 Boiler'';''3.6.1.10 Flue gas cleaning'';''3.6.1.11 Turbine and generator'';''3.6.2 Waste burning'';''3.7 Using industrial waste heat for district heating'';''3.7.1 Heat demand'';''3.7.2 CHP integration to industrial process'';''3.7.3 The potential of CHP in selected industrial sectors'';''3.7.3.1 Chemical and refinery industry'';''3.7.3.2 Wood industry''
Vendor-supplied metadata.
Elsevier
Keywords: Heating from central stations; Air conditioning; Cogeneration of electric power and heat; TECHNOLOGY & ENGINEERING / Construction / Heating, Ventilation & Air Conditioning; Air conditioning; Cogeneration of electric power and heat; Heating from central stations; Electronic books; Electronic books